Konkrete udspil for ukonkrete udslip: politisk kommunikation om klima i 2009 og 2019 - Almlund, Pernille (Politik, 2019)
This article contents a comparison of political communication about climate, as it was among politicians at Christiansborg (the Danish Parliament) in 2009/10 and as it is now in 2019. The comparison is based on interviews with politicians in 2009/10 and the written proposals about climate from the Danish political parties in 2018/19. This is a less traditional methodological comparison, but the article argues that this is exactly a comparison of the most comprehensive information about the parties’ climate politics from these two periods. The analysis, based on a system theoretical approach, shows how the Danish politicians communication about climate has changed from being relatively abstract in 2009 to be relatively concrete in 2019. Moreover, the analysis shows how the contemporary more concrete communication about climate is based on numbers and calculations and shows that numbers and calculations has become the dominating communication form among politicians, when they communicate about climate.